KRITIK ARKOUN ATAS EPISTEMOLOGI ISLAM - M. Fadholi; M. Solikhin (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2018)
The root of Arkoun's epistemology of thought, originated from Arkoun's life that grew at the rapid development of science, both socio-humanities and the natural sciences of the Western world. This momentum is not wasted and left to pass without meaning. So it is not strange that in each of his writings thick with nuances of modern Western terms. The objective of the criticism raised by arkoun is to revive the dynamic and modern Islamic thought, to suit the development of various sciences. According to Arkoun, the understanding and exposure of Islamic studies, whether in the stage of introducing theory, creating concepts, or applying its teachings, must be explained using an interdisciplinary approach. Thus, Islamology can always be aligned with other scientific and rational modern sciences. Or in other languages, Arkoun aspires to an amalgamation of the most valuable element of Islamic reason and modern reason.